Testicular Injury Attenuated by Rapamycin Through Induction of Autophagy and Inhibition of Endoplasmic Reticulum Stress in Streptozotocin-Induced Diabetic Rats - Shi, Wenjiao; Guo, Zhixin; Yuan, Ruixia (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background and Objective: This study investigated whether rapamycin has a protective effect on the testis of diabetic rats by regulating autophagy, endoplasmic reticulum stress, and oxidative stress. Methods: Thirty male Sprague-Dawley rats were randomly divided into three groups: control, diabetic, and diabetic treated with rapamycin, which received gavage of rapamycin (2mg.kg-1.d-1) after induction of diabetes. Diabetic rats were induced by intraperitoneal injection of streptozotocin (STZ, 65mg.Kg-1). All rats were sacrificed at the termination after 8 weeks of rapamycin treatment. The testicular pathological changes were determined by hematoxylin and eosin staining. The protein or mRNA expression of autophagy-related proteins (Beclin1, microtubule-associated protein light chain 3 (LC3), p62), ER stress marked proteins (CCAAT/enhancer-binding protein (C/EBP) homologous protein (CHOP), caspase-12), oxidative stress-related proteins (p22phox, nuclear factor erythroid2-related factor 2 (Nrf2)) and apoptosis-related proteins (Bax, B cell lymphoma-2 (Bcl-2)) were assayed by western blot or real-time fluorescence quantitative PCR. Results: There were significant pathological changes in the testes of diabetic rats. The expression of Beclin1, LC3, Nrf2, Bcl-2 were significantly decreased and p62, CHOP, caspase12, p22phox, and Bax were notably increased in the testis of diabetic rats (P <0.05). However, rapamycin treatment for 8 weeks significantly reversed the above changes in the testis of diabetic rats (P <0.05). Conclusion: Rapamycin appears to produce a protective effect on the testes of diabetic rats by inducing the expression of autophagy and inhibiting the expression of ER-stress, oxidative stress, and apoptosis.
Keywords: testis